Antiphospholipid antibodies in a large population-based cohort: genome-wide associations and effects on monocyte gene expression - Müller-Calleja, Nadine; Rossmann, Heidi; Müller, Christian; Wild, Philipp; Blankenberg, Stefan; Pfeiffer, Norbert; Binder, Harald; Beutel, Manfred E.; Manukyan, Davit; Zeller, Tanja; Lackner, Karl J. (Thrombosis and Haemostasis, 2016)
The antiphospholipid syndrome (APS) is characterised by venous and/ or arterial thrombosis and pregnancy morbidity in women combined with the persistent presence of antiphospholipid antibodies (aPL). We aimed to identify genetic factors associated with the presence of aPL in a population based cohort. Furthermore, we wanted to clarify if the presence of aPL affects gene expression in circulating monocytes. Titres of IgG and IgM against cardiolipin, D2glycoprotein 1 (antiD2GPI), and IgG against domain 1 of D2GPI (anti-domain 1) were determined in approx. 5,000 individuals from the Gutenberg Health Study (GHS) a population based cohort of German descent. Genotyping was conducted on Affymetrix Genome-Wide Human SNP 6.0 arrays. Monocyte gene expression was determined in a subgroup of 1,279 individuals by using the Illumina HT-12 v3 BeadChip. Gene expression data were confirmed in vitro and ex vivo by qRT-PCR. Genome wide analysis revealed significant associations of anti-D2GPI IgG and APOH on chromosome 17, which had been previously identified by candidate gene approaches, and of anti-domain1 and MACROD2 on chromosome 20 which has been listed in a previous GWAS as a suggestive locus associated with the occurrence of anti-D2GPI antibodies. Expression analysis confirmed increased expression of TNFD in monocytes and identified and confirmed neuron navigator 3 (NAV3) as a novel gene induced by aPL. In conclusion, MACROD2 represents a novel genetic locus associated with aPL. Furthermore, we show that aPL induce the expression of NAV3 in monocytes and endothelial cells. This will stimulate further research into the role of these genes in the APS.
Keywords: Antiphospholipid antibodies; genome-wide association study; gene expression; monocytes; cohort study